Acoustic detection of the short pulse call of Brydes whales using time domain features and hidden Marcov models - Wache Ngateu, Gaelle Venessa (Stellenbosch : Stellenbosch University, 2020)
Thesis (MEng)--Stellenbosch University, 2020.